Rare bird documentation form for Greater Scaup at Liscomb Sewage Lagoon, 1987 - Proescholdt, Market al (1987)
Rare bird documentation form fro eight Greater Scaups at Liscomb Sewage Lagoon in Marshall County, IA on March 4, 1987. Epson - sheet feed